The design of library buildings and the Sustainable Development Goals - García-Rodríguez, Araceli; Gómez-Díaz, Raquel (Anuario ThinkEPI, 2022)
The achievement of the Sustainable Development Goals (SDGs) is one of the concerns present in the work of many libraries. In addition to raising awareness, training, collection development, etc., library buildings and infrastructures can also contribute to achieving the goals and objectives set out in the 2030 Agenda. The IFLA, different associations, and organizations have been working along these lines, although the percentage of actions in this vein is still in the minority compared with the other lines mentioned. In this article, the importance of sustainable library buildings is studied, as well as the measures that are being implemented and that seek to contribute to the care of the environment by improving life on the planet
Keywords: Sustainable development goals and libraries; Sustainable libraries; Green libraries; Sustainable library architecture